Global threats, global futures living with declining living standards - Scudder, Thayer; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub., 2010)
Global threats can be expected to cause a global environmental crisis and declining living standards for most people. Threats analyzed include poverty, cultural, economic, political and religious fundamentalism, consumption, population increase and degradation of the global ecosystem. Chapters on the United States, China and Zambia illustrate difficulties that high, middle and low income countries face in addressing such threats. The final chapter examines the type of transformational change required just to reduce the rate and magnitude of future decline.
1. The threat of global poverty -- 2. The threat of fundamentalism -- 3. The threat of environmental degradation -- 4. United States -- 5. People's Republic of China -- 6. Zambia -- 7. Transforming global societies.
Includes bibliographical references (p. 248-275) and index.
Keywords: Cost and standard of living; Cost and standard of living -- Moral and ethical aspects; Economic development; Electronic books